2014
DOI: 10.1007/s13191-014-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anatase Titanium Dioxide Nanoparticles on the Flexural Strength of Heat Cured Poly Methyl Methacrylate Resins: An In-Vitro Study

Abstract: Poly methyl methacrylate (PMMA) resin is the most widely used material for fabrication of dentures since 1937 as it exhibits adequate physical, mechanical and esthetic properties. But one of the major problems faced using this material is that, it is highly prone to plaque accumulation due to surface porosities and its food retentive properties. This in turn increases the bacterial activity causing denture stomatitis. In efforts to impart antimicrobial property to these resins, various nanoparticles (NP) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 16 publications
5
35
0
3
Order By: Relevance
“…Ahmed et al added 1% and 5% 40 nm TiO 2 nanoparticles to traditional heat‐polymerized and high resistance heat‐polymerized acrylic resin powder and reported a decrease in flexural strength values. Nazirkar et al examined the flexural strength values of heat‐polymerized acrylic resin specimens in which 0.5% and 1% 7 nm TiO 2 nanoparticles were added and suggested that flexural strength decreased with the addition of the nanoparticles. In contrast to the aforementioned studies, Harini et al added TiO 2 nanoparticles (1%, 2%, and 5%) to PMMA and revealed that the highest flexural strength values were observed in the group with 5% nanoparticles added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al added 1% and 5% 40 nm TiO 2 nanoparticles to traditional heat‐polymerized and high resistance heat‐polymerized acrylic resin powder and reported a decrease in flexural strength values. Nazirkar et al examined the flexural strength values of heat‐polymerized acrylic resin specimens in which 0.5% and 1% 7 nm TiO 2 nanoparticles were added and suggested that flexural strength decreased with the addition of the nanoparticles. In contrast to the aforementioned studies, Harini et al added TiO 2 nanoparticles (1%, 2%, and 5%) to PMMA and revealed that the highest flexural strength values were observed in the group with 5% nanoparticles added.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical or chemical methods such as melt mixing, mixing in solution, mixing with shear force and high shear force during mechanical mixing, and mixing with ultrasonic mixer are used . Although some investigators have added nanoparticles into the monomer (liquid), some researchers have also mixed them into acrylic resin polymers . In addition, Mc Nally et al explained that SiO 2 cannot be mixed homogeneously with more than 1% using manual mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Powders containing AgNPs of different sizes and concentrations were prepared and mixed with a heat‐polymerizing acrylic (Meliodent, Bayer Dental, Berkshire, UK) monomer liquid (3:1 vol/vol), sonicated (Confident dental equipments Ltd., Bangalore, India) for 1 h at room temperature to achieve proper dispersion, and then poured into 65 mm × 10 mm × 3.3 mm (according to ADA specification no. 12) molds to create 42 heat‐polymerized acrylic resin specimens.…”
Section: Methodsmentioning
confidence: 99%
“…In order to address these issues, manufacturers have recently begun incorporating antimicrobial agents into denture‐base materials, with much focus given to silver nanoparticles (AgNPs) . However, while improving the anti‐infective properties of acrylic dentures is essential, antibacterial agents can have a negative effect on the physical properties of the acrylic substrate, which, when used as a denture base must be able to withstand masticatory forces …”
Section: Introductionmentioning
confidence: 99%
“…It was observed that by increasing the concentration of nanoparticles, the flexural strength of PMMA value increases. In some cases, better flexural strength value was found in comparison with PMMA alone [72,73]. Studies on the improvement of tensile strength concluded that increasing the TiO 2 nanoparticle concentration provided better tensile strength up to some concentration and then the strength decreases [74].…”
Section: Antimicrobial Activitymentioning
confidence: 99%